Malmquist Productivity Index by Extended VIKOR Method Using Interval Numbers. (1st October 2013) - Fallah, Mohammad; Mohajeri, Amir; Najafi, Esmaeil
Abstract : The VIKOR method was developed for multicriteria optimization of complex systems. It determines the compromise ranking list and the compromise solution obtained with the given weights. This method focuses on ranking and selecting from a set of alternatives in the presence of conflicting criteria. Here, the VIKOR method is used for two times t and t + 1 . In order to calculate the progress or regression via Malmquist productivity index, the positive and negative ideals at times t and t + 1 are calculated first. Then we introduce the multi-criteria ranking index based on the particular measure of "closeness" to the ideal solution and calculate the separation of each alternative from the ideal solution at times t and t + 1 . Then we use the Malmquist productivity index to calculate the progress or regression of all alternatives. In this paper, productivity of alternatives available in decision matrix with interval numbers and their improvement or deterioration is researched. To achieve this practical goal, use of extended VIKOR is made to calculate Malmquist productivity index for multicriteria decision-making (MCDM) problem with interval numbers, and by applying Malmquist productivity index, productivity rate of growth for alternatives is calculated. Finally, a numerical example illustrates and clarifies the main results developed in this paper.